1992
DOI: 10.1111/j.1365-2265.1992.tb02324.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of midregional parathyroid hormone‐related protein in hypercalcaemia of malignancy

Abstract: This radioimmunoassay of midregional PTHrP provides high diagnostic sensitivity in the identification of humoral hypercalcaemia of malignancy caused by solid tumours. The assay should therefore be useful in the differential diagnosis of hypercalcaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In contrast to the present findings, others also using assays which recognize epitopes within the 1-74 region found that PTHrP was unstable in EDTA plasma and that addition of protease inhibitors was necessary to prevent progressive degradation.v" In a recent study using a RIA directed at residues 53-84, PTHrP was found to be stable in serum and plasma for several days. 8 There is evidence from cell culture studies that PTHrP produced in vitro is processed within the amino-terminus at residues 20 and 37. 10 Proteolysis at these sites could explain the apparent instability of amino-terminal PTHrP in unseparated blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the present findings, others also using assays which recognize epitopes within the 1-74 region found that PTHrP was unstable in EDTA plasma and that addition of protease inhibitors was necessary to prevent progressive degradation.v" In a recent study using a RIA directed at residues 53-84, PTHrP was found to be stable in serum and plasma for several days. 8 There is evidence from cell culture studies that PTHrP produced in vitro is processed within the amino-terminus at residues 20 and 37. 10 Proteolysis at these sites could explain the apparent instability of amino-terminal PTHrP in unseparated blood.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast endogenous PTHrP53-84 activity is reported to be stable in serum and plasma for up to 3 days at 4°C. 8 Here we describe a systematic comparison of the effects of different anticoagulants and protease inhibitors on the in vitro stability of endogenous PTHrPI-86 from patients with HM as measured by a sensitive, specific immunoradiometric assay (IRMA).2…”
mentioning
confidence: 99%
“…Normal values were obtained for white blood count, platelet count, prothrombin, and partial thromboplastin time, albumin, creatinine, BUN, calcium, phosphate, sodium, potassium, AST, ALT, LDH, total protein, C-reactive protein, and serum protein. Levels for parathyroid hormone (pTH, measured as Nterminal pTH and total pTH), 1.25 (OH)2 vitamin D, and 25 OH vitamin D (determined with commercial radioimmunoassays) were within normal limits, pTH-related activity was not detectable in the serum [1]. Arterial blood pH, pO2, pCO2, bicarbonate, base excess were normal.…”
Section: Case Reportmentioning
confidence: 94%
“…For this assay, 100 l goat antiserum (1:8000), raised against amino acids 53 -84 (Blind et al, 1992), and 100 l reconstituted CM were incubated under non-equilibrium conditions. Synthetic human PTHrP (1 -86) (Bissendorf Biochem., Hannover, Germany) was used as standard and for tracer preparation (Schilling et al, 1996).…”
Section: Midregional Ipthrp Radioimmunoassay (Ria)mentioning
confidence: 99%